A comparative study of 4-hour versus 2-hour action line on who modified partograph - Sinha, Divya; Shrivastava, Sourabh; Shrivastava, Swati (International Journal of Research in Medical Sciences, 2017)
Background: World health organization has promoted modified partograph with action line, 4 hour to left of alert line. While others have used various action line 2, 3, or 4 hours to initiate and guide ‘‘active management’’ decisions. Objectives of the study were to evaluate outcome of labour in terms of caesarean section rate, augmentation of labour and fetal outcome in whom labour has been managed with 4-hour vs 2-hour action line on WHO modified partograph. Methods: This was a randomized, prospective, comparative study. Primigravida, 19-28 years, with single live foetus in vertex presentation without any medical and obstetrical complications, at term pregnancy have been included in the study. Results were compared between Group A, with 100 cases, in whom labour has been managed with WHO modified Partograph with 4-hour action line and Group B, with 100 cases, in whom labour has been managed with that of 2-hour action line. Results: The present study shows that more women in 2-hour arm crossed the action line, compared with the 4-hour arm, and therefore received more interventions to augment labour. Rate of caesarean section is more in group B (11%) than in group A (9%) which is statistically nonsignificant. Conclusions: Neonatal outcome measured with APGAR score at 5 minute, has shown no significant difference in both groups. Therefore, partograph with 2-hour action line doesn’t show any superiority over that of 4-hour action line but to be associated with higher incidence of intervention. Further research is required in this field of active management.